High-conductivity motor winding material and preparation method thereof
By growing graphene on the surface of copper foil and using argon plasma etching and hot pressing sintering processes, a highly conductive graphene/copper composite material was prepared, which solved the problem of high resistance of the motor winding material, and achieved significant improvement in conductivity and Possibility of large-scale production.
Patent Information
- Application Number
- CN202411567043.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-07
AI Technical Summary
The resistance of existing motor winding materials is high, resulting in large heat loss of the motor, making it difficult to meet the needs of high-efficiency motors.
Graphene/copper composite material was used to grow graphene on the surface of the copper foil by CVD, and argon plasma etching and hot pressing sintering process were used to prepare a highly conductive motor winding material.
It significantly reduces the resistance of the motor winding copper wire, improves the conductivity, is suitable for large-scale production, and has a simple process, environmentally friendly and low cost.
Smart Images

Figure CN119400477A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of motor winding material preparation, and in particular to a high-conductivity motor winding material and a preparation method thereof. Background Art
[0002] Electricity is the most important energy source in contemporary society. However, with the development of technology, it is difficult to improve the efficiency of electricity consumption through structural optimization of electrical and electronic equipment. Therefore, designing highly conductive materials has become the main research direction for energy conservation. Copper, as an excellent conductive material, has become an indispensable material in electronic equipment such as motors and cables due to its abundant reserves and low price. It plays an important role in rail transportation, power electronics and military industries.
[0003] When current flows through the motor winding, it will generate heat and cause loss due to the existence of winding resistance. Most windings are made of copper, so it is called "copper loss", which is a kind of active loss. High-efficiency motors are the development direction of motors today, and the best way to improve motor efficiency is to increase the slot fill rate, that is, to reduce the resistance of the winding to reduce the heating loss of the motor winding (i.e. copper loss).
[0004] One of the directions for improving the slot fill rate of motor windings when using flat wire windings to replace round wire windings is that the method uses rectangular wires to improve space utilization, increase the cross-sectional area of copper, and thus reduce the resistance of the windings; however, the space of the core wire slots is limited, and after they are all filled with copper (equivalent to a slot fill rate of 100%, that is, the core wire slots are all filled with copper wires), the resistance can no longer be reduced. Although there are many technologies that further reduce the copper loss of flat wire windings in different ways, for example, the Chinese patent publication number CN110492642A discloses a motor winding with reduced copper loss, and the motor winding reduces the resistance of some winding copper wires at the ends by increasing the cross-sectional area of the end wires; the Chinese patent publication number CN218498909U discloses a motor winding and a motor, and the motor winding improves the slot fill rate of the core by designing winding units arranged at equal angular intervals, but the effects are very limited, so it is urgent to develop a new electrode winding material that can significantly reduce the resistance of the motor winding copper wire.
[0005] Graphene is a two-dimensional carbon material with a π-bond structure similar to carbon nanotubes and a zero-bandgap metal-like property, and a high charge carrier mobility. Copper and graphene have complementary electrical properties. The charge carrier mobility of graphene is four orders of magnitude higher than that of copper, but the charge carrier density is lower, while the charge carrier density of copper is fourteen orders of magnitude higher than that of graphene. Therefore, under the synergistic effect, the composite interface of these two components will have extremely high conductivity. Studies have shown that when graphene contacts the surface of copper lamp metal, it still maintains its zero-bandgap characteristics, while inducing Fermi energy transfer, due to its electron doping effect, increasing the electron concentration in graphene, or obtaining better conductivity. Therefore, graphene / copper composites have great development potential in the field of high-conductivity copper materials and can become a reliable material for reducing the resistance of motor windings.
[0006] Although graphene / copper composites have great application prospects as a new way to reduce the resistance of motor winding copper wires, the conductivity of graphene / copper composites prepared by existing synthesis methods is not high enough and it is difficult to apply them on a large scale to motor winding copper wires, and cannot meet the high standards for winding copper wire materials in the motor winding field. Summary of the invention
[0007] The present invention provides a method for preparing a high-conductivity motor winding material, which comprises the following steps: S1: Mix 0.1 mol / L dilute hydrochloric acid and anhydrous ethanol in a volume ratio of 1:1, place the copper foil in the mixed liquid, and ultrasonically clean it at 20-40°C for 10-30 minutes, repeat the cleaning 2-5 times, and blow dry the surface liquid with nitrogen; S2: Place the dried copper foil in a plasma etcher and reduce the vacuum degree in the etching chamber to 10 -5 After Pa, the copper foil surface is subjected to plasma etching with argon gas, the flow rate of the introduced argon gas is controlled at 10-20 sccm, the etching power is 10-30 W, and the etching time is 10-120 s; S3: The copper foil obtained in step S2 is stacked in a graphite mold and hot-pressed and sintered to obtain a high-conductivity motor winding material.
[0008] The present invention is further configured as follows: the copper foil used in step S1 is a rolled copper foil with a purity of >99% and a thickness of ≤100 μm, and the copper foil area is 1-9 cm 2 , a single layer of graphene synthesized by CVD method is grown on the surface of the copper foil.
[0009] The present invention is further configured as follows: the copper foil is single crystal copper powder; and the graphene coverage on the surface of the copper foil is ≥95%.
[0010] The present invention is further configured as follows: the argon gas used in step S2 is 99.999% high-purity argon gas.
[0011] The present invention is further configured as follows: the hot pressing temperature in step S3 is 600-950° C., the hot pressing pressure is 30-50 MPa, and the hot pressing time is ≥40 min.
[0012] The present invention is further configured as follows: in step S3, before sintering begins, the hot pressing chamber of the hot pressing sintering furnace is first vacuumed until the air pressure in the hot pressing chamber drops to <10Pa, and then argon is introduced into the hot pressing chamber for purge, and then the hot pressing chamber is vacuumed again until the air pressure in the hot pressing chamber drops to <10Pa; the purge process is repeated 3-5 times to ensure that all oxygen in the hot pressing chamber is removed.
[0013] The present invention is further configured as follows: after the gas washing is completed, the copper foil is preheated, the preheating temperature is 400° C., the preheating pressure is normal pressure, and the preheating time is 10 minutes; and hot pressing sintering is performed after the preheating is completed.
[0014] The present invention is further configured as follows: It is characterized in that during the hot pressing sintering process, the pressure of the hot pressing chamber of the hot pressing sintering furnace is maintained at 10 -3 -10 -2 Pa.
[0015] The present invention also provides a high-conductivity motor winding material, which is prepared by the above preparation method.
[0016] The beneficial effects of the present invention are:
[0017] 1. The copper foil with graphene grown by CVD method is treated with argon plasma etching, and then hot-pressed and sintered to obtain a composite material of copper and graphene; the CVD growth method can grow high-quality, large-area graphene on the surface of copper foil in situ, and is suitable for large-scale production. It only needs simple stacking to perform hot pressing, omitting the complex step of evenly dispersing graphene in the copper matrix, and will not cause graphene agglomeration. At the same time, it avoids the damage to the size and purity of graphene caused by mechanical grinding, chemical modification and other processes during the process. Argon plasma etching is conducive to removing water molecules, oxygen molecules and other impurities adsorbed in the air on the surface of graphene, and argon plasma can create vacancy defects in graphene, which can promote the transfer of electrons from copper to graphene, thereby improving the enhancement effect of graphene on the conductive properties of the composite material.
[0018] 2. This method is simple, environmentally friendly and low-cost, does not require toxic and harmful chemical treatment, has a short operation time, and is suitable for large-scale production. This method uses a vacuum hot pressing sintering process to eliminate copper oxidation during the graphene / copper composite material molding process, and gas washing can further eliminate the influence of oxidation on copper and improve the conductivity of the graphene / copper material. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The Raman spectrum of graphene on copper foil after argon plasma etching in Example 2-5 is shown.
[0020] Figure 2 TEM image 1 of the interface in Example 6 is shown.
[0021] Figure 3 The second interface TEM image in Example 6 is shown.
[0022] Figure 4 The third interface TEM image in Example 6 is shown. DETAILED DESCRIPTION
[0023] Those skilled in the art can refer to the content of this article and appropriately improve the process parameters. It is particularly important to point out that all similar replacements and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0024] Example 1
[0025] The present invention provides a method for preparing a high-conductivity motor winding material, comprising the following steps:
[0026] S1: Mix 0.1 mol / L dilute hydrochloric acid with sewage ethanol in a volume ratio of 1:1, place the copper foil in the mixed liquid, and ultrasonically clean it at 20-40°C for 10-30 minutes, repeat the cleaning 2-5 times, and blow dry the surface liquid with nitrogen.
[0027] S2: Place the dried copper foil in a plasma etcher and reduce the vacuum degree in the etching chamber to 10 -5 After Pa, the copper foil surface is subjected to plasma etching with argon gas, the flow rate of the introduced argon gas is controlled at 10-20 sccm, the etching power is 10-30 W, and the etching time is 10-120 s.
[0028] S3: The copper foil obtained in step S2 is stacked in a graphene mold and hot-pressed and sintered to obtain a high-conductivity motor winding material.
[0029] The copper foil used in step S1 is a rolled copper foil with a purity of >99% and a thickness of ≤100 μm, and the area of the copper foil is 1-9 cm 2 The surface of the copper foil has a single layer of graphene synthesized by CVD method. The copper foil is single crystal copper powder; the graphene coverage rate of the copper foil surface is ≥95%.
[0030] The argon gas used in step S2 is 99.999% high purity argon gas.
[0031] In step S3, the hot pressing temperature is 600-950° C., the hot pressing pressure is 30-50 MPa, and the hot pressing time is ≥40 min.
[0032] It should be noted that, before sintering begins in step S3, the hot pressing chamber of the hot pressing sintering furnace needs to be vacuumed until the air pressure in the hot pressing chamber drops to <10Pa, and then argon gas is introduced into the hot pressing chamber for purge, and then the hot pressing chamber is vacuumed again until the air pressure in the hot pressing chamber drops to less than 10Pa; the purge process is repeated 3-5 times to remove all oxygen in the hot pressing chamber.
[0033] After the gas washing is completed, the copper foil is preheated, that is, the copper foil is placed in the graphene mold for preheating, the preheating temperature is 400℃, the preheating pressure is normal pressure, and the preheating time is 10min; after the preheating is completed, hot pressing sintering is performed. Preheating treatment can improve the density of the graphene / copper composite material. During the hot pressing sintering process, the hot pressing chamber of the hot pressing sintering furnace is kept at 10 -3 -10 -2 Pa.
[0034] Example 2
[0035] This embodiment adopts the preparation method disclosed in Example 1 to prepare the high-conductivity motor winding material, which specifically includes the following steps:
[0036] S1: Mix 0.1 mol / L dilute hydrochloric acid and anhydrous ethanol in a volume ratio of 1:1, place the copper foil in the mixed liquid, and perform ultrasonic cleaning at 20°C for 30 min. Repeat the cleaning 5 times, and blow dry the liquid on the surface of the copper foil with nitrogen.
[0037] The copper foil used is a rolled copper foil with a purity of 99.5% and a thickness of 25 μm. The copper foil area is 1 cm 2 , a single layer of graphene synthesized by CVD method is grown on the surface of the copper foil.
[0038] S2: Place the dried copper foil in a plasma etcher and reduce the vacuum degree in the etching chamber to 10 -5 After Pa, the copper foil surface was plasma etched with argon gas, the flow rate of the argon gas was controlled to 10 sccm, the etching power was 30 W, and the etching time was 10 s.
[0039] The argon gas used for etching is 99.999% high-purity argon gas.
[0040] S3: The copper foils obtained in step S2 are stacked in a graphite mold and hot-pressed and sintered to obtain a high-conductivity motor winding material.
[0041] The hot pressing temperature is 650°C, the hot pressing pressure is 50MPa, and the hot pressing time is 40min. Before hot pressing sintering, the hot pressing chamber needs to be purged and the copper foil needs to be preheated.
[0042] Example 3
[0043] This embodiment adopts the preparation method disclosed in Example 1 to prepare the high-conductivity motor winding material, which specifically includes the following steps:
[0044] S1: Mix 0.1 mol / L dilute hydrochloric acid and anhydrous ethanol in a volume ratio of 1:1, place the copper foil in the mixed liquid, and perform ultrasonic cleaning at 30°C for 20 min. Repeat the cleaning 4 times, and blow dry the liquid on the surface of the copper foil with nitrogen.
[0045] The copper foil used is a rolled copper foil with a purity of 99.5% and a thickness of 50 μm. The copper foil area is 4 cm 2 , a single layer of graphene synthesized by CVD method is grown on the surface of the copper foil.
[0046] S2: Place the dried copper foil in a plasma etcher and reduce the vacuum degree in the etching chamber to 10 -5 After Pa, the copper foil surface was plasma etched with argon gas, the flow rate of the argon gas was controlled to 15 sccm, the etching power was 20 W, and the etching time was 20 s.
[0047] The argon gas used for etching is 99.999% high-purity argon gas.
[0048] S3: The copper foils obtained in step S2 are stacked in a graphite mold and hot-pressed and sintered to obtain a high-conductivity motor winding material.
[0049] The hot pressing temperature is 800°C, the hot pressing pressure is 40MPa, and the hot pressing time is 40min. Before hot pressing sintering, the hot pressing chamber needs to be purged and the copper foil needs to be preheated.
[0050] Example 4
[0051] This embodiment adopts the preparation method disclosed in Example 1 to prepare the high-conductivity motor winding material, which specifically includes the following steps:
[0052] S1: Mix 0.1 mol / L dilute hydrochloric acid and anhydrous ethanol in a volume ratio of 1:1, place the copper foil in the mixed liquid, and perform ultrasonic cleaning at 40°C for 10 min. Repeat the cleaning twice, and blow dry the liquid on the surface of the copper foil with nitrogen.
[0053] The copper foil used is a rolled copper foil with a purity of 99.5% and a thickness of 100 μm. The copper foil area is 9 cm 2, a single layer of graphene synthesized by CVD method is grown on the surface of the copper foil.
[0054] S2: Place the dried copper foil in a plasma etcher and reduce the vacuum degree in the etching chamber to 10 -5 After Pa, the copper foil surface was plasma etched with argon gas, the flow rate of the argon gas was controlled to 20 sccm, the etching power was 10 W, and the etching time was 60 s.
[0055] The argon gas used for etching is 99.999% high-purity argon gas.
[0056] S3: The copper foils obtained in step S2 are stacked in a graphite mold and hot-pressed and sintered to obtain a high-conductivity motor winding material.
[0057] The hot pressing temperature is 950°C, the hot pressing pressure is 30MPa, and the hot pressing time is 40min. Before hot pressing sintering, the hot pressing chamber needs to be purged and the copper foil needs to be preheated.
[0058] Example 5
[0059] This embodiment adopts the preparation method disclosed in Example 1 to prepare the high-conductivity motor winding material, which specifically includes the following steps:
[0060] S1: Mix 0.1 mol / L dilute hydrochloric acid and anhydrous ethanol in a volume ratio of 1:1, place the copper foil in the mixed liquid, and ultrasonically clean it at 40°C for 20 minutes. Repeat the cleaning twice, and blow dry the liquid on the surface of the copper foil with nitrogen.
[0061] The copper foil used is a rolled copper foil with a purity of 99.5% and a thickness of 50 μm. The copper foil area is 4 cm 2 , a single layer of graphene synthesized by CVD method is grown on the surface of the copper foil.
[0062] S2: Place the dried copper foil in a plasma etcher and reduce the vacuum degree in the etching chamber to 10 -5 After Pa, the copper foil surface was plasma etched with argon gas, the flow rate of the argon gas was controlled to 15 sccm, the etching power was 15 W, and the etching time was 120 s.
[0063] The argon gas used for etching is 99.999% high-purity argon gas.
[0064] S3: The copper foils obtained in step S2 are stacked in a graphite mold and hot-pressed and sintered to obtain a high-conductivity motor winding material.
[0065] The hot pressing temperature is 950°C, the hot pressing pressure is 50MPa, and the hot pressing time is 40min. Before hot pressing sintering, the hot pressing chamber needs to be purged and the copper foil needs to be preheated.
[0066] Example 6
[0067] This embodiment adopts the preparation method disclosed in Example 1 to prepare the high-conductivity motor winding material, which specifically includes the following steps:
[0068] S1: Mix 0.1 mol / L dilute hydrochloric acid and anhydrous ethanol in a volume ratio of 1:1, place the copper foil in the mixed liquid, and perform ultrasonic cleaning at 40°C for 10 min. Repeat the cleaning twice, and blow dry the liquid on the surface of the copper foil with nitrogen.
[0069] The copper foil used is a rolled copper foil with a purity of 99.5% and a thickness of 50 μm. The copper foil area is 1 cm 2 , a single layer of graphene synthesized by CVD method is grown on the surface of the copper foil.
[0070] S2: Place the dried copper foil in a plasma etcher and reduce the vacuum degree in the etching chamber to 10 -5 After Pa, the copper foil surface was plasma etched with argon gas, the flow rate of the argon gas was controlled to 15 sccm, the etching power was 15 W, and the etching time was 60 s.
[0071] The argon gas used for etching is 99.999% high-purity argon gas.
[0072] S3: The copper foils obtained in step S2 are stacked in a graphite mold and hot-pressed and sintered to obtain a high-conductivity motor winding material.
[0073] The hot pressing temperature is 950°C, the hot pressing pressure is 50MPa, and the hot pressing time is 60min. Before hot pressing sintering, the hot pressing chamber needs to be purged and the copper foil needs to be preheated.
[0074] Example 7
[0075] This embodiment adopts the preparation method disclosed in Example 1 to prepare the high-conductivity motor winding material, which specifically includes the following steps:
[0076] S1: Mix 0.1 mol / L dilute hydrochloric acid and anhydrous ethanol in a volume ratio of 1:1, place the copper foil in the mixed liquid, and perform ultrasonic cleaning at 40°C for 10 min. Repeat the cleaning twice, and blow dry the liquid on the surface of the copper foil with nitrogen.
[0077] The copper foil used is a rolled copper foil with a purity of 99.5% and a thickness of 50 μm. The copper foil area is 9 cm 2 , a single layer of graphene synthesized by CVD method is grown on the surface of the copper foil.
[0078] S2: Place the dried copper foil in a plasma etcher and reduce the vacuum degree in the etching chamber to 10 -5After Pa, the copper foil surface was plasma etched with argon gas, the flow rate of the argon gas was controlled to 15 sccm, the etching power was 15 W, and the etching time was 60 s.
[0079] The argon gas used for etching is 99.999% high-purity argon gas.
[0080] S3: The copper foils obtained in step S2 are stacked in a graphite mold and hot-pressed and sintered to obtain a high-conductivity motor winding material.
[0081] The hot pressing temperature is 950°C, the hot pressing pressure is 50MPa, and the hot pressing time is 120min. Before hot pressing sintering, the hot pressing chamber needs to be purged and the copper foil needs to be preheated.
[0082] Comparative Example 1
[0083] This comparative example is based on Example 6, using ordinary rolled copper foil without CVD growth of graphene, and other conditions remain unchanged.
[0084] The graphene copper foil after argon etching in Example 2-5 was tested by Raman spectroscopy. The results are as follows: Figure 1 The G peak and 2D peak of Examples 2-5 prove that the graphene on the surface of the copper foil is a single-layer graphene, wherein the reason why the 2D peak is small in Example 5 is that the etching time is too long and the graphene is seriously damaged; the D peak in Examples 2-3 proves that defects are successfully introduced into the graphene by argon off-etching, while in Example 4, due to insufficient etching time and power, the defect introduction is not significant.
[0085] Under the test condition of 25° C., the conductivity of the high-conductivity motor winding materials prepared in Examples 2-7 and Comparative Example 1 was tested using a Van der Pauw test system. The results are shown in Table 1 below. Table 1
[0086] The morphology of the high-conductivity motor winding material prepared in Comparative Example 6 was characterized, and the results were as follows: Figure 2-4 As shown, there is an obvious two-phase interface inside the material, and the layered structure of graphene at the interface is clearly observed, indicating that the obtained high-conductivity motor winding material is a graphene / copper composite material, and the graphene is curled and stacked during the hot pressing process; the test structures of Examples 2-4, 6, and 7 are basically consistent with the test structure of Example 5.
[0087] Example 8
[0088] This embodiment discloses a high-conductivity motor winding material, which is prepared by the preparation method described in Example 1.
[0089] In summary, the present invention uses argon plasma etching to treat copper foil with graphene grown by CVD method, and then obtains a composite material of copper foil and graphene by hot pressing and sintering; the CVD growth method can grow high-quality, large-area graphene on the surface of copper foil in situ, and is suitable for large-scale production, and only needs simple stacking to perform hot pressing, omitting the complex step of evenly dispersing graphene in the copper matrix, and will not cause agglomeration of graphene, while avoiding the damage to the size and purity of graphene by mechanical grinding, chemical modification and other processes in the process. Argon plasma etching is conducive to removing water molecules, oxygen molecules and other impurities adsorbed in the air on the surface of graphene, and argon plasma can create vacancy defects in graphene, and these defects can promote the transfer of electrons from copper to graphene, thereby improving the enhancement effect of graphene on the conductive properties of the composite material.
[0090] The method is simple, environmentally friendly and low-cost, does not require toxic and harmful chemical treatment, has a short operation time, and is suitable for large-scale production. The method adopts a vacuum hot pressing sintering process, which can eliminate the oxidation of copper during the molding process of the graphene / copper composite material, and the gas washing can further eliminate the influence of oxidation on copper and improve the conductivity of the graphene / copper material.
[0091] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be within the scope of protection of the present invention.
Claims
1. A method for preparing a high-conductivity motor winding material, characterized in that: The following steps are included: S1: Mix 0.1 mol / L dilute hydrochloric acid and anhydrous ethanol in a volume ratio of 1:1, place the copper foil in the mixed liquid, and perform ultrasonic cleaning at 20-40°C for 10-30 min, repeat the cleaning 2-5 times, and blow dry the surface liquid with nitrogen; S2: Place the dried copper foil in a plasma etcher and reduce the vacuum degree in the etching chamber to 10 -5 After Pa, the copper foil surface is subjected to plasma etching with argon gas, the flow rate of the introduced argon gas is controlled at 10-20 sccm, the etching power is 10-30 W, and the etching time is 10-120 s; S3: The copper foil obtained in step S2 is stacked in a graphite mold and hot-pressed and sintered to obtain a high-conductivity motor winding material.
2. The method for preparing a high-conductivity motor winding material according to claim 1, characterized in that: The copper foil used in step S1 is a rolled copper foil with a purity of >99% and a thickness of ≤100 μm, and the area of the copper foil is 1-9 cm 2 , a single layer of graphene synthesized by CVD method is grown on the surface of the copper foil.
3. The method for preparing a high-conductivity motor winding material according to claim 2, characterized in that: The copper foil is single crystal copper powder; the graphene coverage rate on the surface of the copper foil is ≥95%.
4. The method for preparing a high-conductivity motor winding material according to claim 1, characterized in that: The argon gas used in step S2 is 99.999% high-purity argon gas.
5. The method for preparing a high-conductivity motor winding material according to claim 1, characterized in that: The hot pressing temperature in step S3 is 600-950° C., the hot pressing pressure is 30-50 MPa, and the hot pressing time is ≥40 min.
6. The method for preparing a high-conductivity motor winding material according to claim 1, characterized in that: In step S3, before sintering begins, the hot pressing chamber of the hot pressing sintering furnace is first vacuumed until the pressure of the hot pressing chamber drops to less than 10Pa, and then argon gas is introduced into the hot pressing chamber for gas washing, and then the hot pressing chamber is vacuumed again until the pressure of the hot pressing chamber drops to less than 10Pa; Repeat the purge process 3-5 times to ensure that all oxygen in the autoclave is removed.
7. The method for preparing a high-conductivity motor winding material according to claim 6, characterized in that: After the gas washing is completed, the copper foil is preheated at a temperature of 400°C, a preheating pressure of normal pressure, and a preheating time of 10 minutes; after the preheating is completed, hot pressing sintering is performed.
8. The method for preparing a high-conductivity motor winding material according to claim 7, characterized in that: During the hot pressing sintering process, the pressure in the hot pressing chamber of the hot pressing sintering furnace is maintained at 10 -3 -10 -2 Pa.
9. A high conductivity motor winding material, characterized in that: The method is prepared according to any one of claims 1 to 8.
Citation Information
Patent Citations
Method for preparing needle-like manganese dioxide / graphene composite electrode material
CN105448531A
Preparation method for graphene-reinforced copper-based composite material
CN108193065A
Preparation method of multi-layer graphene thin film
CN108517510A
High-strength and high-conductivity copper-based composite material and preparation method thereof
CN111145960A
Preparation method of multilayer graphene
CN111591980A